Improving Early Childhood English Speaking Ability through Storyreading Method (Indonesian Journal of Early Childhood Education Studies, 2022)
This research is about the application of the storyreading method to children aged 5-6 years, as a method that can stimulate early childhood speaking skills. The purpose of this study is to describe the improvement of speaking skills in English through the storyreading method. The researcher conducted an action research using the Pelton model (2010) with three actions on seven children of group B of Eka Saputra Kindergarten in Cileunyi District, Kab. Bandung. Data were collected through observation and documentation in the form of photos regarding learning activities. The results showed an improvement in children's English speaking ability after using the storyreading method. This is shown from the data from actions one to three which shows a significant increase in the aspect of mentioning vocabulary by 45.4%, expressing simple question words by 85.7% and answering simple questions by 41.8%. This study proves that the storyreading method can improve children's English speaking skills.